Box Design Selection for Portable Minapadi Based on Hydrostatic and Thermal Loading Simulation - Tri Julianto, Baskoro; Setiawan , Budi Indra; Saptomo, Satyanto Krido (Jurnal Keteknikan Pertanian, 2024)
Land conversion has led to the encouragement of urban farming, which is practiced on a small area of land. The innovation of Nonpowered Automatic Fertigator that has been used to support urban farming continues to be developed, especially for the portable paddy-fish integrated farming model. Because of this, a study of supporting equipment is needed, one of which is a good cribs design. Tests were carried out on the materials that make up the cribs to determine the mechanical properties of the material in the form of Young’s modulus where from ten test objects the average elastic modulus was obtained at 15582.19 MPa. The mechanical properties obtained are entered into a computer simulator to be applied to the simulation of the cribs. There are two cribs designs that were tested by being loaded with hydrostatic loads and thermal loads. The results of the simulation showed that the first cribs was rated better than the second cribs with a smaller maximum total deformation indicator than the second cribs design under extreme hydrostatic loading conditions.